Determinants of Price Fluctuation for Cooking Oil Commodity in Aceh Province, Indonesia - Hadi Arisyah Putra; Chenny Seftarita; Suriani Suriani (International Journal of Business, Economics, and Social Development, 2021)
Aceh Province is still one of the regions in Indonesia whose primary commodities are still largely dependent on other regions that can cause uncontrolled fluctuations in the price especially cooking oil product. One step to overcome these problems is to make accurate price fluctuation predictions so preventive actions can be taken to minimize error estimation of these fluctuations so appropriate policies can be applied. This study focuses on analyzing of forecasting fluctuations in cooking oil prices and the influence of its determinants in the Aceh Province, Indonesia. Price forecasting uses the Autoregressive Integrated Moving Average (ARIMA) approach and determinant estimation uses the Ordinary Least Square (OLS) method. The data used in this study is time-series monthly data from January 2016 to December 2020 from Statistics Indonesia publication. The results of price forecasting show that the monthly price of cooking oil for 2021 and 2022 tends to increase. In early 2021, it is predicted that the price of cooking oil will be in the range of IDR14,500/kg and at the end of the year and early 2022 it is predicted to touch the price range of IDR15,500/kg. Then at the end of 2022 it is predicted that the price of cooking oil will reach IDR17,000/kg. Furthermore, the results of the econometric estimation show that all of the variable determinants have a significant effect on cooking oil prices fluctuations. The variable price of raw materials and the price index received by farmers were found to have a positive effect, while the rainfall variable was found to have a negative effect on cooking oil price fluctuation. According to these findings, it is hoped that the Aceh Provincial Government will be able to take strategic policies on the predicted prices and determinant of variables that have been proven to have a significant effect on cooking oil prices so in the future price fluctuations can be more stable and supply of goods can be maintained, as well as increase the competitiveness of provincial agricultural products.